Gazing into the Future through a VDU: Communications, Information Technology, and Law Teaching. - Alldridge, Peter; Mumford, Ann (Journal of Law & Society, 1998)
The article deals with the interaction of computers, information technology, and legal education. It considers the technical achievements of communications and information technology (C&IT) in the practice and teaching of law, then the jurisprudential paradigms which underlie these issues. To the extent to which law is conceived as a form of information, existing assumptions about the theory, practice, and teaching of law are challenged. Where, on the other hand, law is regarded as a collection of rules, reversal to formalism, driven by C&IT, is identified as a concern for socio-legal scholars. Other concerns addressed by this article include the exclusive economics of the C&IT revolution, the power dynamics of technophobia, and the interaction of computers and gender. The article concludes with suggestions for alternative visons of the future of C&IT and legal education.